The role of the English teacher in the development on the teaching-learning process. - Sani Vallejo, Katherin Lizbeth (2023)
The roles that a teacher currently plays reflect great benefits in the teaching and learning process, which are: in the first instance of motivator, being a reference so that students are not afraid to make mistakes and instead help them to discover personal strategies for studying English. On the other hand, there is the role of the guide, who seeks to train students through their own learning, without neglecting their teaching work. This study was carried out in the Unidad Educativa Camilo Gallegos Toledo. It has been determined that the role of the English teacher in the development of the teaching and learning process is of great value in the educational environment, both in the construction of individual and collective knowledge of the students, who are currently considered the main actors in this field. Therefore, the role of the teacher at Octavo Año Paralelo “A “classes is evidenced by the application of some of them. This research focused on analyzing the roles that would be most productive for the development of the teaching and learning process. Therefore, the research has a qualitative-quantitative and descriptive-exploratory approach. The data collection techniques were survey and observation sheet. The population considered for the research were 27 students of the Octavo Año Paralelo "A" of the Educational Unit. The results of this research were descriptive and exploratory, as it investigated the performance of the different roles as motivator, guide and facilitator of the English teacher in the classroom.